A metastable liquid precursor phase of calcium carbonate and its interactions with polyaspartate - Bewernitz, M.; Gebauer, Denis; Long, J.; Cölfen, H.; Gower, L. (R S C Publications, 2012)
Invertebrate organisms that use calcium carbonate extensively in the formation of their hard tissues have the ability to deposit biominerals with control over crystal size, shape, orientation, phase, texture, and location. It has been proposed by our group that charged polyelectrolytes, like acidic proteins, may be employed by organisms to direct crystal growth through an intermediate liquid phase in a process called the polymer-induced liquid-precursor (PILP) process. Recently, it has been proposed that calcium carbonate crystallization, even in the absence of any additives, follows a non-classical, multi-step crystallization process by first associating into a liquid precursor phase before transition into solid amorphous calcium carbonate (ACC) and eventually crystalline calcium carbonates. In order to determine if the PILP process involves the promotion, or stabilization, of a naturally occurring liquid precursor to ACC, we have analyzed the formation of saturated and supersaturated calcium carbonate-bicarbonate solutions using Ca 2+ ion selective electrodes, pH electrodes, isothermal titration calorimetry, nanoparticle tracking analysis, 13C T 2 relaxation measurements, and 13C PFG-STE diffusion NMR measurements. These studies provide evidence that, in the absences of additives, and at near neutral pH (emulating the conditions of biomineralization and biomimetic model systems), a condensed phase of liquid-like droplets of calcium carbonate forms at a critical concentration, where it is stabilized intrinsically by bicarbonate ions. In experiments with polymer additive, the data suggests that the polymer is kinetically stabilizing this liquid condensed phase in a distinct and pronounced fashion during the so called PILP process. Verification of this precursor phase and the stabilization that polymer additives provide during the PILP process sheds new light on the mechanism through which biological organisms can exercise such control over deposited CaCO 3 biominerals, and on the potential means to generate in vitro mineral products with features that resemble biominerals seen in nature. © The Royal Society of Chemistry 2012.